The Influence of Self-Efficacy Through Work Motivation on Commitment to the Organization - Prabowo, Budhi; Moeins, Anoesyirwan; Yusnita, Nancy (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – The purpose of this study was to find the influence of self-efficacy through motivation on commitment to the organization at Posyantek DKI Jakarta through an analysis of the magnitude of the direct influence of self-efficacy on work motivation, the direct influence of work motivation on commitment to the organization and the indirect influence of self-efficacy through work motivation on commitment to the organization. Methodology/approach – The method used is a quantitative method. The population in this study was 258 and the sample used was 158 Posyantek administrators. While the data analysis method of testing research instruments uses validity tests, reliability tests. Data analysis techniques consist of descriptive analysis of respondent characteristics and SEM PLS analysis. Findings – The results of this study indicate thatself-efficacy variables have a positive effect on motivation variables or it can be said that the higher the self-efficacy, the higher the motivation, conversely the lower the self-efficacy, the lower the motivation, the motivation variables have a positive effect on commitment variables to the organization or it can be said that the higher the motivation, the higher the performance, conversely the lower the motivation, the lower the performance and self-efficacy has a significant effect on commitment to the organization mediated by motivation.